Технологічний принцип визначення економічної безпеки будівельного підприємства - Федосова, О. В.; Молодід, О. О. (Ways to Improve Construction Efficiency, 2012)
The technological principle of determining the economic security of the construction company, which allows us to consider production as a technological system in which is olated the dominant technological component and led technical, resource material and personnel components. The character of relation sand relationships between dominant and wingman functional components, which allows us to offer current complex quasilinear technoeconometric relationships determine economic security